The challenges of community policing in maintaining community security: the case of Harar City, Ethiopia - Abrha, Alexander Haymanot (Policing and society, 2024)
The adoption of community policing was expected to bring a paradigm shift in preventing crime and disorder. However, regardless of the practice of community policing as a strategy to maintain public security, the programme faces several challenges that hinder its proper implementation. The purpose of this article is to examine the challenges of community policing implementation in Harar City, Ethiopia. This article employed a qualitative research approach with a grounded theory design. The article used both primary and secondary data sources and the study participants were selected using a purposive sampling technique. Data was collected using key informant interviewees, focus group discussions, non-participant observation, and document analysis. The thematic analysis method was applied during the data analysis process. The study revealed that conceptual and practical, institutional, infrastructural challenges and political constraints derived from the community, the police organisation, and the government agencies limit the successful practices of community policing for maintaining public security in the study area. It is, therefore, recommended that the community, police organisation, government agencies, and other stakeholders have to coordinate and collaborate to alleviate or at least minimise the challenges of community-based policing in Harar City.